The Effect of Nutritional Status and Workload Intensity on Fatigue and Productivity Levels Among Production Unit Workers at PT X in East Jakarta, DKI Jakarta - Nada Kamilah; Diniyah Kholidah; Rizki Mustika Riswari (Health Science Udinus, 2026)
Achieving health in the workplace is greatly influenced by how the workforce fulfills its nutritional requirements. Every worker needs nutrients according to the type of work they do. Heavy work requires consuming more calories compared to medium and light work, this is basically to achieve a balance between nutritional intake and workload. Fulfillment of nutrition that is not appropriate to the workload can cause a decrease in productivity and increase the potential for experiencing work fatigue. The aim of this research is to analyze the influence of nutritional status and workload intensity on the level of fatigue and work productivity of workers at PT X. The research method used is quantitative with multiple linear regression analysis. The way to obtain research data is by field observation and filling out questionnaires. Based on output the statistical significance value for the simultaneous influence of X1 and > F table 2.92. There is a significant influence between nutritional status and workload on the level of fatigue and there is a significant influence between nutritional status and workload on the level of work productivity